2015
DOI: 10.1111/jphp.12483
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of human UDP-glucuronosyltransferases responsible for the in-vitro glucuronidation of arctigenin

Abstract: UGT1A9, UGT2B7 and UGT2B17 were the major isoforms responsible for the 4'-O-glucuronidation of AR in HLM, while UGT2B7 and UGT2B17 were the major contributors to this biotransformation in HIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…And in intestine and liver, AG could be extensively metabolized to one mono-glucuronide and undergo a first-pass metabolism during the absorption process. Therefore, elimination ability is strong (Gao et al, 2014a,b; Xin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And in intestine and liver, AG could be extensively metabolized to one mono-glucuronide and undergo a first-pass metabolism during the absorption process. Therefore, elimination ability is strong (Gao et al, 2014a,b; Xin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The substrates remaining of AG in four species liver microsomes were human (62 ± 6.36%) > beagle dog (25.9 ± 3.24%) > rat (15.7 ± 9%) > monkey (3.69 ± 0.12%). It was reported that AG could be metabolized to one mono-glucuronide in human liver microsomes (Xin et al, 2015). And AG could be metabolized to arctigenic acid and arctigenin-4′- O -glucuronide by the first pass effect in intestine of rats (Gao et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both arctiin and arctigenin were demonstrated to exert strong inhibitory effects on the activity of UGT1A3, 1A9, 2B7, and 2B15. UGT1A3, 1A9, and 2B7 were involved in the metabolism of arctigenin (Xin et al , ), possibly explaining why arctiin and arctigenin exhibited strong inhibition toward these three UGT isoforms. It should be noted that UGT2B15 is not the UGT isoform participating in the metabolism of arctigenin, indicating poor substrate property of arctigenin for UGT2B15.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study performed by Xin et al showed that UGT1A9, 2B7, and 2B17 mainly contributed to the metabolism of arctigenin in the liver, and UGT2B7 and UGT2B17 mainly contributed to the metabolism of arctigenin in the intestine (Xin et al , ), indicating the good interaction between arctigenin‐like structure and the activity cavity of several UGT isoforms. Therefore, the recent study aims to investigate the inhibition of arctiin and arctigenin on the activity of UGT isoforms.…”
Section: Introductionmentioning
confidence: 99%